”Rotasi” (Relaksasi Otot Progresif dengan Musik Relaksasi) untuk Menurunkan Skala Nyeri dan Tekanan Darah Lansia dengan Hipertensi - Ni Luh Putu Dian Yunita Sari; Ni Made Dwi Ayu Martini; I Kadek Prastikanala (FORIKES, 2023)
Elderly people with hypertension are one of the groups at high risk during the COVID-19 pandemic. Hypertensive elderly people are also prone to experiencing pain complaints which have the potential to influence blood pressure fluctuations. This phenomenon requires complementary approaches and interventions which are expected to be able to complement antihypertensive drugs. The aim of this study was to determine the effect of “Rotasi” (Relaksasi Otot Progresif dengan Musik Relaksasi) / (Progressive Muscle Relaxation with Relaxation Music) on the pain scale and blood pressure of elderly people with hypertension. This study implemented a pretest-posttest design with control group. The population in this study were all elderly people who experienced hypertension in the working areas of community health centers throughout Tabanan Regency, Bali. The sample was selected using a purposive sampling technique, with a sample size of 64 people (32 people per group). The intervention was given in one session with a duration of 30 minutes, namely